2022
DOI: 10.1371/journal.pone.0264786
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the active ingredients and pharmacological mechanisms of Porana sinensis Hemsl. Against rheumatoid arthritis using network pharmacology and experimental validation

Abstract: Background Porana sinensis Hemsl. has been widely used as a substitute for Erycibes Caulis to treat rheumatoid arthritis (RA) in traditional Chinese medicine (TCM). However, little is known about the active ingredients and pharmacological mechanisms that mediate the action of P. sinensis against RA. Methods The compounds contained in P. sinensis were analyzed by Q Exactive Focus mass spectrometer. The active constituents and pharmacological mechanism of P. sinensis against RA were clarified using a network p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Additionally, esculetin (10-100 µg/ml) inhibits IL-6 production in TNF-α stimulated human osteosarcoma MG-63 cells (67). Esculetin (1-10 µg/ml) can also inhibit the release of inflammatory mediators, such as NO, TNF-α, IL-1β, IL-6 and monocyte chemoattractant protein-1 (MCP-1) in LPS-induced RAW 264.7 cells (68)(69)(70)(71). Further studies demonstrate that the anti-inflammatory effect of esculetin is associated with inhibiting the NF-κB signaling pathway (72)(73)(74)(75)(76)(77).…”
Section: Anti-inflammatory Activities Of Esculetin and Esculinmentioning
confidence: 99%
“…Additionally, esculetin (10-100 µg/ml) inhibits IL-6 production in TNF-α stimulated human osteosarcoma MG-63 cells (67). Esculetin (1-10 µg/ml) can also inhibit the release of inflammatory mediators, such as NO, TNF-α, IL-1β, IL-6 and monocyte chemoattractant protein-1 (MCP-1) in LPS-induced RAW 264.7 cells (68)(69)(70)(71). Further studies demonstrate that the anti-inflammatory effect of esculetin is associated with inhibiting the NF-κB signaling pathway (72)(73)(74)(75)(76)(77).…”
Section: Anti-inflammatory Activities Of Esculetin and Esculinmentioning
confidence: 99%
“…HIF-1α increases the production of inflammatory cytokines and promotes angiogenesis in rheumatic arthritis patients ( Park et al, 2015 ). We reported that the 40% ethanol extract of P. sinensis alleviates rheumatoid arthritis by regulating the PI3K-Akt and HIF-1 signaling pathways ( Hu et al, 2022 ).…”
Section: Pharmacological Activities Of Porana Plantsmentioning
confidence: 99%
“…COX-2 is a critical enzyme that catalyzes the conversion of arachidonic acid to prostaglandins, and this study confirmed the inhibitory effect of extract 1 on PGE2 synthesis. We reported that 40% ethanol extract of P. sinensis (extract 3 ) inhibits the release of inflammatory mediators (NO, TNF-α, IL-1β, and IL-6) in LPS-induced RAW 264.7 cells ( Hu et al, 2022 ). Extract 3 attenuates the severity, pathological changes, and release of cytokines (IL-6 and HIF-1α) during rheumatoid arthritis progression by regulating the PI3K/Akt and HIF-1 pathways ( Hu et al, 2022 ).…”
Section: Pharmacological Activities Of Porana Plantsmentioning
confidence: 99%
“…Using the PubChem (https://pubchem.ncbi.nlm.nih.gov/) database [11], all validated compounds collected were converted into standard Canonical SMILES format, and the SMILES format files were imported into SWISS (http://www. swisstargetprediction.ch/) [12]and the Superpred website (http://prediction.charite.de/), and set the property "homo sapiens" to predict the targets of the compounds.…”
Section: Prediction Of Potential Targetsmentioning
confidence: 99%